Nuevas tecnologías de la información y la comunicación: Integración en el aula de idiomas - Quesada Pacheco, Allen (2015)
The purpose of this article is to present a case study on the use of new technologies such as the integration of the Internet in the English as a Foreign Language (EFL) classroom, with a group of EFL students in the School of Modern languages at the University of Costa Rica. The results of the study suggest that it is necessary to integrate the Internet resources in English classes as a tool to practice and leam English. Thus, this article presents Internet-based projects in the EFL context at a public university in Costa Rica.